Karakterisasi Simplisia dan Ekstrak Etanol Daun Pegagan (Centella asiatica (L.) Urban) - Hanifah Arini Putri, Hanifah Arini Putri; Dina Mulyanti (Jurnal Riset Farmasi, 2023)
Abstract. Gotu kola leaves (Centella asiatica (L.) Urban) are known contain chemical compounds that are beneficial to health. The purpose of this research was to knowing the characteristics of simplicia and ethanol extract of gotu kola leaves. Simplicia characteristics include organoleptic observation and examination of standard simplicia parameters, include specific parameters and non-specific parameters. While the characteristics of the ethanol extract of gotu kola leaves include organoleptic observations and the percent (%) value of extract rendement. Extraction was using the maceration method with 70% ethanol solvent. Determination of the chemical compound in simplicia and extracts was carried out by phytochemicals screening. The results of organoleptic observations showed that the leaves of gotu kola had a dark green color, had a characteristic odor of gotu kola leaves, and had a fan-like shape with rounded leaf tips. The results of standard simplicia parameter examination were water-soluble extract content of 15.21%, ethanol-soluble extract content of 21.24%, water content of 7.9%, drying losses of 9.29%, total ash content of 13.15%, and acid insoluble ash content 0.71%. The results of characteristic observations of the ethanol extract of gotu kola leaves had dark brown color, the smell of the extract is typical of gotu kola leaves, the form of the extract is thick, and the extract rendement was 32.93%. Simplicia and ethanol extract of gotu kola leaves contain compounds belonging to the group of flavonoids, saponins, polyphenols, tannins, and steroids. Abstrak. Daun pegagan (Centella asiatica (L.) Urban) diketahui memiliki kandungan senyawa kimia yang bermanfaat bagi kesehatan. Tujuan dari penelitian ini adalah untuk mengetahui karakteristik dari simplisia dan ekstrak etanol daun pegagan. Karakteristik simplisia meliputi pengamatan secara organoleptik dan pemeriksaan parameter standar simplisia yaitu parameter spesifik dan parameter non spesifik. Sedangkan karakteristik ekstrak etanol daun pegagan meliputi pengamatan organoleptik dan penentuan nilai persen (%) rendemen hasil dari ekstraksi. Ekstraksi dilakukan menggunakan metode maserasi dengan pelarut etanol 70%. Penentuan golongan senyawa kimia pada simplisia dan ekstrak dilakukan dengan skrining fitokimia. Hasil pengamatan organoleptik simplisia menunjukkan bahwa daun pegagan memiliki warna hijau tua, dengan bau khas daun pegagan, dan bentuknya seperti kipas dengan ujung daun membulat. Hasil pemeriksaan parameter standar simplisia yaitu kadar sari larut air sebesar 15,21%, kadar sari larut etanol 21,24%, kadar air 7,9%, susut pengeringan 9,29%, kadar abu total 13,15%, dan kadar abu tidak larut asam 0,71%. Hasil pengamatan karakteristik terhadap ekstrak etanol daun pegagan diantaranya memiliki warna coklat kehitaman pekat, bau ekstrak yaitu khas daun pegagan, bentuk ekstrak adalah kental, nilai %rendemen hasil dari ekstraksi sebesar 32,93%. Simplisia dan ekstrak etanol daun pegagan mengandung golongan senyawa flavonoid, saponin, polifenol, tannin, dan steroid.